2020
DOI: 10.1099/mgen.0.000440
|View full text |Cite
|
Sign up to set email alerts
|

Exploration into the origins and mobilization of di-hydrofolate reductase genes and the emergence of clinical resistance to trimethoprim

Abstract: Trimethoprim is a synthetic antibacterial agent that targets folate biosynthesis by competitively binding to the di-hydrofolate reductase enzyme (DHFR). Trimethoprim is often administered synergistically with sulfonamide, another chemotherapeutic agent targeting the di-hydropteroate synthase (DHPS) enzyme in the same pathway. Clinical resistance to both drugs is widespread and mediated by enzyme variants capable of performing their biological function without binding to these drugs. These mutant enzymes were a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 78 publications
2
29
0
Order By: Relevance
“…Antifolate antibiotics exert their action by inhibiting purine metabolism, and thereby DNA and RNA synthesis. Trimethoprim is a dihydrofolate reductase (DHFR) inhibitor (blocking tetrahydrofolic acid formation by dihydrofolic acid, an essential step of folate biosynthesis, which in turn is involved in the generation of many nucleotides and amino acids), while sulfonamides are known dihydropteroate synthase (DHPS) inhibitors (halting the conversion of para-aminobenzoate or PABA to dihydropteroate; including sulfamethoxazole, commonly used in combination with trimethoprim, and sulfonamides) [ 185 ]. Resistance against diaminopyrimidines in A. baumannii infections is mainly conferred by trimethoprim-resistant dihydrofolate reductases DfrA1, DfrA5, DfrA7, DfrA10, DfrA12, DfrA14, DfrA16, DfrA17, DfrA19, DfrA20, DfrA27, and DfrB1 (encoded by dfrA1 , dfrA5 , dfrA7 , dfrA10 , dfrA12 , dfrA14 , dfrA16 , dfrA17 , dfrA19 , dfrA20 , dfrA27 , and dfrB1 , respectively) [ 97 ].…”
Section: Resistance To Othersmentioning
confidence: 99%
“…Antifolate antibiotics exert their action by inhibiting purine metabolism, and thereby DNA and RNA synthesis. Trimethoprim is a dihydrofolate reductase (DHFR) inhibitor (blocking tetrahydrofolic acid formation by dihydrofolic acid, an essential step of folate biosynthesis, which in turn is involved in the generation of many nucleotides and amino acids), while sulfonamides are known dihydropteroate synthase (DHPS) inhibitors (halting the conversion of para-aminobenzoate or PABA to dihydropteroate; including sulfamethoxazole, commonly used in combination with trimethoprim, and sulfonamides) [ 185 ]. Resistance against diaminopyrimidines in A. baumannii infections is mainly conferred by trimethoprim-resistant dihydrofolate reductases DfrA1, DfrA5, DfrA7, DfrA10, DfrA12, DfrA14, DfrA16, DfrA17, DfrA19, DfrA20, DfrA27, and DfrB1 (encoded by dfrA1 , dfrA5 , dfrA7 , dfrA10 , dfrA12 , dfrA14 , dfrA16 , dfrA17 , dfrA19 , dfrA20 , dfrA27 , and dfrB1 , respectively) [ 97 ].…”
Section: Resistance To Othersmentioning
confidence: 99%
“…The strain E-072658 was resistant to sulfamethoxazole as it harbours the sul2 gene required for resistance to this drug [92]. Interestingly, all of the environmental isolates except for E-072658 were moderately or fully resistant to trimethoprim, despite lacking the trimethoprim resistance gene dfrA, which encodes a trimethoprim-insensitive homologue of the sensitive dihydrofolate reductase encoded by folA [93,94]. Four isolates (Ex003, B9, 10-3 and 10-4) were resistant to florfenicol and chloramphenicol, most likely due to the presence of genes encoding efflux-mediated resistance mechanisms, including major facilitator super family (MFS) transporters [95,96].…”
Section: Antibiotic Resistance Profilingmentioning
confidence: 99%
“…Factors associated with TMP resistance are far more complex in the clinical isolates. A recent study has shown the contribution of mobile dfrA genes to TMP resistance in the emerging pathogen Acinetobacter baumannii and its association to chromosomal folA genes in rapidly mobilizing novel mutations ( Sánchez-Osuna et al, 2020 ). The study shows how sulfonamide resistance in general extends to TMP with generalized chromosomal resistance determinants predating the origin of several genera and several clusters of resistance genes disseminated broadly among clinical isolates.…”
Section: Introductionmentioning
confidence: 99%